2016
DOI: 10.1111/cdev.12608
|View full text |Cite
|
Sign up to set email alerts
|

How School Norms, Peer Norms, and Discrimination Predict Interethnic Experiences Among Ethnic Minority and Majority Youth

Abstract: This research tests how perceived school and peer norms predict interethnic experiences among ethnic minority and majority youth. With studies in Chile (654 nonindigenous and 244 Mapuche students, M = 11.20 and 11.31 years) and the United States (468 non-Hispanic White and 126 Latino students, M = 11.66 and 11.68 years), cross-sectional results showed that peer norms predicted greater comfort in intergroup contact, interest in cross-ethnic friendships, and higher contact quality, whereas longitudinal results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 49 publications
(60 reference statements)
5
90
0
Order By: Relevance
“…This study uses two distinct but complementary frameworks. First, we draw from intergroup contact theory (Allport, ; Pettigrew & Tropp, ), which posits that youth will be more disposed toward intergroup contact when there are supportive norms (i.e., authority sanction) in the setting (see Tropp et al., ). Although the school investigated in this study is not implementing specific prejudice reduction approaches, it is engaged in practices that are meant to promote inclusiveness.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…This study uses two distinct but complementary frameworks. First, we draw from intergroup contact theory (Allport, ; Pettigrew & Tropp, ), which posits that youth will be more disposed toward intergroup contact when there are supportive norms (i.e., authority sanction) in the setting (see Tropp et al., ). Although the school investigated in this study is not implementing specific prejudice reduction approaches, it is engaged in practices that are meant to promote inclusiveness.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, Tropp et al. () found that adolescents’ perceptions of their peers’ norms toward intergroup contact were positively related with their own intergroup attitudes, including their feelings of comfort and interest in interethnic friendships. These peer dynamics may be further complicated by broader, potentially distinct social norms of their shared context, like their school or classroom.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, there has been a movement to consider more closely the role of peer and school norms for youth. In particular, examining how perceptions of both peer and school norms differently predict outcomes including intergroup attitudes, aggressive tendencies, and interest in engaging in intergroup contact (Tropp et al ., ). This study extends this body of research by examining the differing role of peer and school norms in influencing the extent to which adolescents engage in frequent and quality contact and the consequence that this contact has on both positive and negative intergroup behaviours in the context of ethno‐religious relations in Northern Ireland.…”
Section: Introductionmentioning
confidence: 97%
“…This study extends this body of research by examining the differing role of peer and school norms in influencing the extent to which adolescents engage in frequent and quality contact and the consequence that this contact has on both positive and negative intergroup behaviours in the context of ethno‐religious relations in Northern Ireland. This is under the premise that norms influence the extent to which individuals engage or have interest in intergroup interactions (Tropp et al ., ) and that they are associated with intergroup behaviours, both positive (e.g., altruism and helping; Berkowitz, ) and negative (e.g., aggressive tendencies; Nesdale & Lawson, ).…”
Section: Introductionmentioning
confidence: 99%